Improving Higher Order Thinking Skills (HOTS) with Project Based Learning (PjBL) Model Assisted by Geogebra. (February 2020) - Suherman,; Prananda, M R; Proboningrum, D I; Pratama, E R; Laksono, P; Amiruddin,
Abstract: The 21st century requires learning that provides a project-based and constructive experience so that higher order thinking skills can be increased. The objective of this study was to improve HOTS with Project Based Learning (PjBL) model assisted by Geogebra. Quasi-Experimental was used as the method, with simple random sampling as the sampling technique. Data collecting techniques used were the test method to see the improvement of HOTS. The hypothetical test used was one-way ANOVA with a significant level of 5% and N-gain was used to determine the improvement of HOTS. The results show that there is an influence from the Geogebra-assisted Project Based Learning model on higher order thinking skills. In addition, the average score of the class taught by using the Geogebra-assisted Project Based Learning (PjBL) model was higher than the non-Project-Based Learning (PjBL) class with an increase of 0.643 in the medium category. It means that learning can achieve the desired goals, the teacher must plan learning well, and the PjBL model can be made as a learning solution in the 21st century.